Affirmation of municipal educational policies in a regionalized territory: the case of the Autonomous Region of Madeira - Alves, Eduardo (2019)
Currently, the Portuguese State intends to start a new and broader phase in the relationship with the Municipalities, expanding the range of competencies in the education sector. Portugal is, however, a regionalized unitary state. Any initiative in this area can not lose the importance of the competences of the Autonomous Regions. In the case of Madeira in Education, the process of expansion of municipal competences can not fail to consider the already existing competences. Therefore, the competence expansion, everything will have to win if it is conducted through bottom-up policies through interaction with local actors, instead of top-down policies where distrust will lead to the reduction of the dynamics of autonomy and the loss of the quality of the educational service.Key-words: educational administration; decentralization; municipalization; regional autonomy; regionalization and regional educational policies.